Censorship detected in IR (Iran) - Voidly (Voidly Global Censorship Index, 2025)
CRITICAL severity censorship detected in Iran. Data sourced from CensoredPlanet.
Censorship Incident ID: IR-2025-0008. Severity: critical. Confidence: 75%